Haro15: Is it actually a low metallicity galaxy? - Firpo, Verónica (2009)
We present a detailed study of the physical properties of the nebular material in multiple knots of the blue compact dwarf galaxy Haro 15. Using long slit and echelle spectroscopy, obtained at Las Campanas Observatory, we study the physical conditions (electron density and temperature), ionic and total chemical abundances of several atoms, reddening and ionization structure. The latter was derived by comparing the oxygen and sulphur ionic ratios to their corresponding observed emission line ratios (the η and η' plots) in different regions of the galaxy. Applying direct and empirical methods for abundance determination, we perform a comparative analysis between these regions.